Aspectos do pensamento algébrico revelados por professores-estudantes de um curso de formação continuada em educação matemática - Castro, Taís Freitas de Carvalho (2009)
This study aims to analyse the professors-students algebraic thoughts aspects in a Mathematics Education Continuing Formation Course when solving some Algebra problems. This objective have theses questions to be answered: Which are the professors-students algebraic thoughts aspects? Which are the algebraic language justifications used? Did the technology using help to solve at least one of the problems? In what? We used the theory by Fiorentini, Miorim e Miguel (1993) and Fiorentini, Fernandes e Cristóvão (2005) to discuss about algebraic thoughts. The data were colected during a post-graduation class in Mathematics Education when the algebraic thoughts were used in order to solve some mathematical problems. Fifiteen professors took part in the study that is why the nomination professors-students. From the colected forms there are written solutions on the problems and a quizz where mathematical explations and justifications were required. The conclusions show that many aspects of the algebric thoughts classificators are shown in the professors-students procedures and they didn t always use the algebraic language when solving Algebra problems. Besides, the study shows that they had difficulties in explaining the reasons of their procedures and in justifying mathematical resolutions. When comes to technology, we could notice that it not always helps in the mathematical problems resolution